2010
DOI: 10.1007/s11144-010-0238-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ethylene polymerization using FI-like zirconium based catalysts

Abstract: Three FI-like Zr-based catalysts, Bis[1-[(phenylimino)methyl]-2-naphtholato]zirconium(IV) dichloride (1), Bis[1-[(mesitylimino)methyl]-2-naphtholato]zirconium(IV) dichloride (2) and Bis[1-[(2,6-diisopropylphenyl)imino] methyl-2-naphtholato]zirconium(IV) dichloride (3) were prepared by changing the ligand from salicylaldehyde imine ligand, which is a well known FI catalysts, to 2-hydroxynaphthalene-1-carbaldehyde imine ligand and used for polymerization of ethylene. Triisobutylaluminum (TIBA) and methylaluminox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Catalyst systems based on bis(phenoxy-imine) complexes of Ti(IV), Zr(IV) and MAO are effective catalysts for polymerization of ethylene and propylene [19,33,34,38,50,[51][52][53][54]. Detailed 13 C NMR analysis of end-groups in polypropylene prepared with several catalysts of this type showed unusual chemical and regio-effects [52,55].…”
Section: Polymerization Of Higher α-Olefin With Fi Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalyst systems based on bis(phenoxy-imine) complexes of Ti(IV), Zr(IV) and MAO are effective catalysts for polymerization of ethylene and propylene [19,33,34,38,50,[51][52][53][54]. Detailed 13 C NMR analysis of end-groups in polypropylene prepared with several catalysts of this type showed unusual chemical and regio-effects [52,55].…”
Section: Polymerization Of Higher α-Olefin With Fi Catalystmentioning
confidence: 99%
“…Ahmadjo and coworkers [53] (3) were prepared by changing the ligand from salicylaldehyde imine ligand, to 2-hydroxynaphthalene-1-carbaldehyde imine ligand and used for polymerization of ethylene (Figure 14) [53]. It has been reported that introducing the sterically bulky isopropyl groups enhances molecular weight of the resulting polymer through destabilization of -agostic interaction due to the steric repulsion betweenhydrogen of the growing polymer and isopropyl leading to decrease the -H elimination [34].…”
Section: Modification Of the Fi Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene polymerization behavior using catalysts 3, 4 and 5 were studied under different reaction times (Table 1, entries 20-34) and temperatures (entries [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The highest activity of catalyst 5 was obtained at 10 °C (31200 Kg PE mol cat -1 h -1 ).…”
Section: Effects Of Polymerization Conditionsmentioning
confidence: 99%
“…Therefore, much effort has been directed towards the development of highly active catalysts, following the group 4 metallocene catalysts. In consequence, quite a few highly active catalysts based on both early and late transition metal complexes have been developed [7][8][9][10][11][12][13][14]. There are, however, only a few examples of titanium complexes displaying high ethylene polymerization activities [15][16][17][18][19], though titanium metal is the major player in highly active heterogeneous Ziegler-Natta catalysts.…”
Section: Introductionmentioning
confidence: 99%